Visual and Thematic Analysis of Brand Equity Research through Bibliometric Study - Judijanto, Loso (Westscience Press, 2025)
This study conducts a comprehensive visual and thematic analysis of brand equity research using bibliometric techniques through VOSviewer. Drawing on data retrieved from the Scopus database, the analysis examines publication trends, influential authors, countries, and thematic clusters from the earliest available year to 2025. Co-citation, co-authorship, and keyword co-occurrence maps reveal that foundational constructs (such as brand loyalty, brand awareness, perceived quality, and purchase intention) remain central to the field, while emerging topics like green brand equity, social media marketing, and brand experience are gaining prominence. Country collaboration analysis highlights the United States as the leading hub of global research partnerships, bridging contributions from developed and emerging economies. Overlay visualization demonstrates a thematic evolution from traditional marketing strategy toward sustainability and digital branding, whereas density mapping underscores the dominance of consumer-based brand equity frameworks alongside expanding research into technology-driven and socially responsible branding. The findings offer practical guidance for brand managers and policymakers, while contributing to the theoretical understanding of how brand equity research has evolved and where future opportunities lie.